2-tert-Butyl-4-methyl-6-(1,3-oxazinan-1-ylmethyl)phenol - Lei, Wen-Jun; Zhan, Shu-Zhong; Ng, S.W. (International Union of Crystallography, 2010)
The title compound, C(16)H(25)NO(2), which was synthesized by a Mannich reaction route, is a rare example of an organic compound containing the six-membered oxazine ring. The ring adopts a chair conformation and the N atom is pyramidal. The N atom serves as a hydrogen-bond acceptor to the phenolic OH group.